Plasmodium vivax Duffy Binding Protein-Based Vaccine: a Distant Dream - Kar, Sonalika; Sinha, Abhinav (Frontiers in Cellular and Infection Microbiology, 2022)
The neglected but highly prevalent Plasmodium vivax in South-east Asia and South America poses a great challenge, with regards to long-term in-vitro culturing and heavily limited functional assays. Such visible challenges as well as narrowed progress in development of experimental research tools hinders development of new drugs and vaccines. The leading vaccine candidate antigen Plasmodium vivax Duffy Binding Protein (PvDBP), is essential for reticulocyte invasion by binding to its cognate receptor, the Duffy Antigen Receptor for Chemokines (DARC), on the host’s reticulocyte surface. Despite its highly polymorphic nature, the amino-terminal cysteine-rich region II of PvDBP (PvDBPII) has been considered as an attractive target for vaccine-mediated immunity and has successfully completed the clinical trial Phase 1. Although this molecule is an attractive vaccine candidate against vivax malaria, there is still a question on its viability due to recent findings, suggesting that there are still some aspects which needs to be looked into further. The highly polymorphic nature of PvDBPII and strain-specific immunity due to PvDBPII allelic variation in Bc epitopes may complicate vaccine efficacy. Emergence of various blood-stage antigens, such as PvRBP, PvEBP and supposedly many more might stand in the way of attaining full protection from PvDBPII. As a result, there is an urgent need to assess and re-assess various caveats connected to PvDBP, which might help in designing a long-term promising vaccine for P. vivax malaria. This review mainly deals with a bunch of rising concerns for validation of DBPII as a vaccine candidate antigen for P. vivax malaria.